Предмет: Алгебра, автор: votindanil

Можно без решения, главное ответ.

Приложения:

Ответы

Автор ответа: snow99
1
8)
( \frac{x + 3}{ {x}^{2} - 3x }  +  \frac{x - 3}{ {x}^{2} + 3x } ) \times  \frac{9x -  {x}^{3} }{ {x}^{2} + 9 }  = ( \frac{x + 3}{x(x - 3)}  +  \frac{x - 3}{x(x + 3)} ) \times  \frac{x(9 -  {x}^{2} )}{ {x}^{2} + 9 }  =  \frac{ {(x + 3)}^{2} +  {(x - 3)}^{2}  }{x(x - 3)(x + 3)}  \times  \frac{x(3 - x)(3 + x)}{ {x}^{2}  + 9}  =  \frac{ {x}^{2} + 6x + 9 +  {x}^{2} - 6x + 9  }{x(x - 3)(x + 3)}  \times  \frac{ - x(x - 3)(x + 3)}{ {x}^{2}  + 9}  =  \frac{ - (2 {x}^{2}  + 18)}{ {x}^{2}  + 9}  =  \frac{ - 2( {x}^{2}  + 9)}{ {x}^{2} + 9 }  =  - 2
Ответ: -2.

9)
( {x}^{ - 1}  +  {y}^{ - 1} ) \times  \frac{2xy}{{x}^{2}  + 2xy +  {y}^{2} }  = ( \frac{1}{x}  +  \frac{1}{y} ) \times  \frac{2xy}{ {(x + y)}^{2} }  =  \frac{y + x}{xy}  \times  \frac{2xy}{ {(x + y)}^{2} }  =  \frac{2}{x + y}
Похожие вопросы
Предмет: Химия, автор: cr1shtianoron